Enacting a social ecology: radically embodied intersubjectivity - McGann, Marek (Frontiers in Psychology, 2014)
Embodied approaches to cognitive science frequently describe the mind as “world-involving”, indicating complementary and interdependent relationships between an agent and its environment. The precise nature of the environment is frequently left ill-described, however, and provides a challenge for such approaches, particularly, it is noted here, for the enactive approach which emphasises this complementarity in quite radical terms. This paper argues that enactivists should work to find common cause with a dynamic form of ecological psychology, a theoretical perspective that provides the most explicit theory of the psychological environment currently extant. In doing so, the intersubjective, cultural nature of the ecology of human psychology is explored, with the challenges this poses for both enactivist and ecological approaches outlined. The theory of behavior settings (Barker, 1968; Schoggen, 1989) is used to present a framework for resolving some of these challenges. Drawing these various strands together an outline of a radical embodied account of intersubjectivity and social activity is presented.